2023
DOI: 10.3390/v15051091
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Gene Orthology in Baculoviridae: An Exhaustive Analysis to Redefine the Ancestrally Common Coding Sequences

Abstract: Baculoviruses are entomopathogens that carry large, double-stranded circular DNA genomes and infect insect larvae of Lepidoptera, Hymenoptera and Diptera, with applications in the biological control of agricultural pests, in the production of recombinant proteins and as viral vectors for various purposes in mammals. These viruses have a variable genetic composition that differs between species, with some sequences shared by all known members, and others that are lineage-specific or unique to isolates. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The SpobMNPV has all the 38 core genes (Cerrudo et al, 2023) (Table S3) reported in baculoviruses and is highly similar to their TA B L E 1 Whole-genome comparison of SpobMNPV isolate with some selected baculoviruses. 138) 62 ( 15) 78 ( 136) 79 ( 14) 79 ( 14)…”
Section: Annotation and Gene Content Of Spobmnpv Isolate Genomementioning
confidence: 90%
See 1 more Smart Citation
“…The SpobMNPV has all the 38 core genes (Cerrudo et al, 2023) (Table S3) reported in baculoviruses and is highly similar to their TA B L E 1 Whole-genome comparison of SpobMNPV isolate with some selected baculoviruses. 138) 62 ( 15) 78 ( 136) 79 ( 14) 79 ( 14)…”
Section: Annotation and Gene Content Of Spobmnpv Isolate Genomementioning
confidence: 90%
“…Although p24 is identified as a conserved gene among lepidopteran baculoviruses (Rohrmann, 2019), further analysis of the function of p24 is required in various baculoviruses to clarify its conserved role in OB shape among baculovirus species (Kokusho & Katsuma, 2021). However, before a recent report (Cerrudo et al, 2023), the presence of 38 core genes in baculoviruses has been considered widely for evolutionary studies.…”
Section: Abbreviationmentioning
confidence: 99%
“…A recent study, which considered all available baculoviral genome data, proposed a similar outcome solely based on genetic distance criteria. This study explored sequences ranging between 81,755 and 178,733 base pairs and encompassed between 89 and 183 protein-coding genes [ 12 ]. Baculoviruses possess their own machinery for transcription and replication, and all reported members share at least 39 orthologous protein genes [ 12 , 13 , 14 ].…”
Section: Baculovirus Biologymentioning
confidence: 99%
“…This study explored sequences ranging between 81,755 and 178,733 base pairs and encompassed between 89 and 183 protein-coding genes [ 12 ]. Baculoviruses possess their own machinery for transcription and replication, and all reported members share at least 39 orthologous protein genes [ 12 , 13 , 14 ]. Interestingly, despite the extensive protein gene content in baculoviral genomes, the presence of non-coding RNA genes has also been observed, including those that encode microRNAs (miRNAs) [ 15 ] and even transfer RNAs (tRNAs) [ 16 ].…”
Section: Baculovirus Biologymentioning
confidence: 99%
See 1 more Smart Citation